RETRACTED: Platelet-Derived Exosomal MicroRNA-25-3p Inhibits Coronary Vascular Endothelial Cell Inflammation Through Adam10 via the NF-κB Signaling Pathway in ApoE−/− Mice - Yao, Ye; Sun, Weidong; Sun, Qingfeng; Jing, Bao; Liu, Siqi; Liu, Xinyu; Shen, Guanghui; Chen, Ru; Wang, Haiyang (Frontiers in Immunology, 2019)
Introduction: Coronary artery disease originates from the blockage of the inner walls of the coronary arteries due to a plaque buildup. Accumulating studies have highlighted the role of microRNAs (miRs) delivered by exosomes in the progression of coronary artery disease. Thus, the current study was to elucidate the role and mechanism by which miR-25-3p influences oxidized low density lipoprotein (ox-LDL)-induced coronary vascular endothelial cell (CVEC) inflammation. Methods: Primarily isolated CVECs were treated with ox-LDL to induce inflammation. Atherosclerosis models induced in ApoE-/- mice, the peripheral blood platelet exosomes (PLT-Exo) were extracted and induced by thrombin, followed by co-culture with CVECs. The relationship between miR-25-3p and A disintegrin and metalloprotease 10 (Adam10) as well as the involvement of the NF-κB signaling pathway was evaluated. In order to evaluate the effect of PLT-Exo containing miR-25-3p on ox-LDL-induced CVEC inflammation, lipid accumulation and fibrosis, miR-25-3p mimic/inhibitor (in vitro), miR-25-3p agomir (in vivo) and si-Adam10 were delivered. Results: miR-25-3p was expressed poorly in ox-LDL-induced CVECs and vascular tissues, but exhibited high levels of expression in thrombin-induced PLT-Exo of atherosclerosis models of ApoE-/- mice. CVECs endocytosed PLT-Exo upregulated the miR-25-3p expression. Adam10 was identified as a target gene of miR-25-3p. The thrombin-induced activated PLT-Exo carrying miR-25-3p reduced Adam10 expression to inhibit ox-LDL-induced CVEC inflammation and lipid deposition through downregulating levels of α-smooth muscle actin, Collagen I a1, Collagen III a1, triglycerides, total cholesterol, interleukin (IL)-1β, IL-6 and tumor necrosis factor-α. Furthermore, the NF-κB signaling pathway participated in the inhibitory effect of PLT-Exo carrying miR-25-3p. Conclusion: Collectively, PLT-Exo overexpressing miR-25-3p attenuates ox-LDL-induced CVEC inflammation in ApoE-/- mouse models of atherosclerosis.